Uji Aktivitas Larvasida Ekstrak Etanolik Daun Serai Wangi (Cymbopogon nardus L.) terhadap Larva Culex sp. Instar III - Eka Cahya Nugraha; Tri Mulyowati; Rinda Binugraheni (Biomedika, 2019)
Culex sp. larvae is a vector of filariasis. The prevention effort is by controlling the presence of Culex sp. Citronella grass is known to contain secondary metabolite which is useful as plant-based insecticides. This research was conducted to determine the toxicity of the ethanolic extract of citronella grass on the mortality of Culex sp. III instar.The research method used was an experimental method with a completely randomized design (CRD) research design, the treatment that was tried was reagent control; negative control; 250 ppm; 353 ppm; 498 ppm; 702 ppm; 991 ppm; 1397 ppm; 1970 ppm, three replications for each treatment. Variables observed were larvae mortality in various concentrations. Larvae mortality was calculated after 24 hours. The data obtained were analyzed using the kruskal wallis test and the man whitney test with SPSS 21 application to determine the LC50value using probit analysis.The results indicate that the ethanolic extract of citronella grass functioned as larvasideonCulex sp. larvae III instar. The higher the concentration of citronella grass extract used, the greater the mortality percentage of Culex sp. larvae. III instar. The concentration of 991 ppm was the most effective concentration and the LC50value was 1036,54 ppm. The conclusion of this research is the ethanolic extract of citronella grass (Cymbopogonnardus L.) has larvicidal activity on Culex sp. larvae. III instar.